Pt.4 - "Legge, James (tr.)" (Delhi, 1978)
Six volumes of the series on sacred books of the east are devoted to the study of chinas main religions confucianism, taoism and buddhism are the three main religions of china translated in six volumes are the main texts of these religions
Keywords: Confucianisus